PENGARUH PERANCANGAN KONTEN TIKTOK VINA MULIANA (@VMULIANA) TERHADAP KEBUTUHAN INFORMASI PADA KALANGAN FOLLOWERS - FIRDI, M; Cindoswari, Ageng Rara (LPPM Universitas Putera Batam, 2023)
The role of Tiktok @Vmuliana certainly has several information needs that intersect withvarious aspects, including cognitive needs, affective needs, comprehensive needs, socialneeds, and the need to share with followers. The purpose of this study is to find out howmuch influence @Vmuliana has on meeting information needs among followers. Thisresearch is a quantitative descriptive study. informant determination technique usingpurposive sampling. The technique of obtaining samples using the simple random samplingmethod using the slovin formula obtained by 100 respondents. Data collection techniquesuse questionnaires, libraries and documentation. Data validity using correlation productmoment. Data analysis techniques use simple regression analysis. This goal is to find outthe influence of Vina Muliana's Tiktok content on meeting the information needs of followers.The respondents in this study were follower of Vina Muliana's Tiktok account with thepersistence of the number of samples calculated using the formula. The theory used is theUse and Gratification theory which has the assumption that the use of media plays an activerole in choosing and using which media is appropriate to meet its needs, in this case it is aninformation need